A Critique of the Meter of Persian Poems in the Tarikh –e- Baihaqi in Version of Yahaghi-sayyedi - Yadullah Mohammadi; Seyed Ahmad Parsa (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
“Tarikh –e- Baihaqi” is one of the Persian proses taught in two undergraduate and postgraduate courses in Persian language and literature. Having a good correction makes it easier to teach. So far, six corrections have been made in “Tarikh –e- Baihaqi”. Two recent corrections have been favored by researchers. The present study compares the recording of the Persian poems of Tarikh –e- Baihaqi in two versions of the Tarikh –e- Baihaqi of Yahaghi-Sayyedi and Fayyaz and tries to assess the accuracy of the recordings and the accuracy of the copy editors by examining the harmony of these poems with the content. For this purpose, in addition to using the prosodic rules of the Persian language, attempted have been made to use transcripts, attention to the imagination, textual consistency, authentic corrections of the poets’ divans, transcripts. The research method is descriptive-analytical. Data were analyzed by the library and document analysis using the content analysis method. The result shows that understanding the true meaning of the verses, linking them to the historical statements of the text and understanding them correctly depends on the correct meter of the verses, which unfortunately has not been adequately addressed in the correction of some of the verses. Metrical studies indicate that the correction of Yahaghi-Sayyedi despite more manuscripts is less accurate at his disposal.